1983
DOI: 10.1007/bf00689733
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the pectoralis muscle during hibernation in the big brown bat,Eptesicus fuscus

Abstract: Summary.The relationship between pectoralis muscle mass and body mass is examined throughout the annual body mass cycle in Eptesicusfuscus in order to evaluate muscle maintenance during hibernation. E. fuscus undergoes large fluctuations in body mass during the year due to pregnancy, parturition, prehibernation fattening, and hibernation (Table 1). Parallel changes occur in pectoralis muscle mass and total pectoralis protein mass (Table 2). The strong correlation between log pectoralis mass and log body mass (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
(29 reference statements)
1
21
0
Order By: Relevance
“…The sartorius muscle from six-month aestivators maintained CSA at control levels and then significantly decreased by 22% after nine months of aestivation (Fig.3B). These reductions in whole muscle CSA and mass are significant and they are not dissimilar to previous findings on hibernating mammals, which range from 14% to 63% (Steffen et al, 1991;Yacoe, 1983;Wickler et al, 1987;Reid et al, 1995;Wickler et al, 1991). The cruralis muscle, the largest of the four muscles examined and a powerful jumping muscle, did not exhibit any change in CSA during aestivation (Fig.3D).…”
Section: B L Mantle and Otherssupporting
confidence: 73%
See 1 more Smart Citation
“…The sartorius muscle from six-month aestivators maintained CSA at control levels and then significantly decreased by 22% after nine months of aestivation (Fig.3B). These reductions in whole muscle CSA and mass are significant and they are not dissimilar to previous findings on hibernating mammals, which range from 14% to 63% (Steffen et al, 1991;Yacoe, 1983;Wickler et al, 1987;Reid et al, 1995;Wickler et al, 1991). The cruralis muscle, the largest of the four muscles examined and a powerful jumping muscle, did not exhibit any change in CSA during aestivation (Fig.3D).…”
Section: B L Mantle and Otherssupporting
confidence: 73%
“…Few studies have explored the effect of dormancy on muscle disuse atrophy in skeletal muscle (for reviews, see Carey et al, 2003;Shavlakadze and Grounds, 2006). In general, hibernators exhibit some level of muscle atrophy, although to a lesser extent than would be observed in humans under the same conditions (Yacoe, 1983;Wickler et al, 1987;Steffen et al, 1991;Wickler et al, 1991). There appear to be no published studies that examine the relationship between muscle fibre composition and biomechanical function and how this relationship might influence muscle disuse atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies conducted on hamsters (Deveci and Egginton, 2002b;James et al, 2011), ground squirrels (Cotton and Harlow, 2010;Gao et al, 2012;James et al, 2013;Nowell et al, 2011;Steffen et al, 1991;Yang et al, 2014) and bats (Kim et al, 2000;Lee et al, 2008;Yacoe, 1983a) have shown relatively minor changes in muscle mass and protein content during hibernation, with most reporting 5-30% decreases in mass and 5-15% decreases in protein (Table 1). There is, however, some variation depending on species, specific muscles and sampling period.…”
Section: Morphological Changes During Hibernationmentioning
confidence: 99%
“…Collectively, these studies indicate that losses of muscle mass, protein and fiber size are typically small during hibernation. Furthermore, the ratio of skeletal muscle mass to body mass is maintained (James et al, 2013;Van Dyke et al, 2007;Yacoe, 1983a) or even improved (Hindle et al, 2014;Yang et al, 2014) following hibernation. Interestingly, animals may emerge from hibernation with greater functional capacity in regards to locomotor performance due to the much greater loss of adipose tissue in relation to skeletal muscle changes.…”
Section: Morphological Changes During Hibernationmentioning
confidence: 99%
“…During dormancy the animal is primarily reliant upon stored lipids, with protein meeting additional energy demands (Harlow et al, 2001;Pakay et al, 2002;Pedler et al, 1996;Seymour, 1973;Tinker et al, 1998;van Beurden, 1980). Muscle comprises the largest protein store in the body, therefore catabolism of muscle tissue as an energy substrate during hibernation and aestivation may contribute to muscle disuse atrophy (Steffen et al, 1991;Wickler et al, 1987;Wickler et al, 1991b;Yacoe, 1983). Additionally, it has been demonstrated that protein synthesis is downregulated during dormancy, which may further compound the atrophic effects of dormancy on skeletal muscle (Frerichs et al, 1998;Fuery et al, 1998;Pakay et al, 2002).…”
Section: Introductionmentioning
confidence: 99%